Proposal for transfer from Appendix I to Appendix II of the Crocodylus acutus population for the Conference of the Parties COP17 CITES (2016)
Transfer from Appendix I to Appendix II of the population of Crocodylus acutus (Cuvier, 1807) of the Distrito Regional de Manejo Integrado del rea de Manglar de la Baha de Cispata y Sector Aledao del Delta Estuarino del Ro Sin, located in the department of Cordoba, Republic of Colombia, in accordance with Resolution Conf. 11.16 (Rev. CoP15) on ranching and trade in ranched specimens